Computer-Assisted Elaboration of Job Histories - Martin, J.M.; Mouaddib, A.; Robaux, P. (Methods of Information in Medicine, 1990)
Three ways are proposed to help the occupational physician in constructing a worker’s job history or Curriculum Laboris (CL) with a PC. The quality and, therefore, the usefulness of any job history is greatly conditioned by the method and quality of data collection. The Curriculum Laboris method explained in a previous article has been briefly summarized as a basis of departure. Then, the workers who were submitted to special medical surveillance were considered. After this, the scrolling menu technique was applied in the elaboration of a job history. Finally, the authors show how the representation of company organization by means of a job exposure matrix (JEM) can help to efficiently elaborate job histories.
Keywords: Job History; Curriculum Laboris; Occupational Risks; Surveillance; Computer